Compact multiband antennas on low temperature co-fired ceramic (TCC) technology / Hadi Jumaat - Jumaat, Hadi (2015)
In recent years, the developments of wireless system that can operate over multiband frequency with compact size have enormous growth. In this project, LTCC technology is benefited for miniaturization of multiband antennas for short range medical sensor application. Three antenna designs on LTee multilayer substrate have been proposed. They are Aperture Coupled antenna (ACA), Dual Patch Microstrip Antenna (DPMA) and Triple Band Off-Center Fed Microstrip Antenna (TBOCFMA). In aperture coupled antenna structure, observation on the controlling parameters of the aperture coupled antenna on LTCC multilayer substrate package is conducted to investigate the effect of aperture slot at various layers with different height. The proposed concept of this idea is simulated on Ferro A6M microstrip ceramic substrate and compared with the simulated of aperture coupled antenna on Flame Retardent 4 (FR-4) substrate at operating frequency of 5.8 GHz. Thus, the best location of the ground plane that contains the aperture slot has been adopted in DPMA design. In DPMA, dual band frequency spectrum operating at 5.8 GHz and 6.3 GHz frequency band has been proposed. This design develops dual radiating patch at the top and bottom of the overall substrate with the aperture slot at the ground between patches. The second radiating patch is designed to place at the feedline that is innovated from the aperture coupled structure. This design then fabricated and a good agreement was achieved between the simulation and measurement results. Meanwhile, the third design TBOCFMA operating at 5.8 GHz, 6.3 GHz and 10 GHz frequency band is presented. This design adopted the dual radiating patch with the aperture slot at the ground between second radiation patch in DPMA. The feedline then was fed with an off-centred feedline technique to create another resonant frequency. Fabrication also has been done for this design for feasibility of study purpose. The complexity of the LTee technology fabrication process is covered in this thesis.